Autonomic Innervation to the Head: Animations and a Self-Testing Guide - Bob Hutchins (Association of American Medical Colleges, 2009)
Abstract This resource is a set of animations and self-testing guides to be used by medical or dental students learning the autonomic pathways to the head. Autonomics within the head are traditionally difficult for students to learn, and few texts or atlases provide both the pathway and the anatomical locations of these nerves in one condensed presentation. Lesions along any part of these pathways will lead to functional deficits and are often stressed during the students' learning. The autonomics to the head are organized into each of the four parasympathetic ganglia (ciliary, submandibular, pterygopalatine, and otic), demonstrating their preganglionic origin within the brainstem, preganglionic termination within the ganglion, and postganglionic termination. The sympathetics are then shown (or referred to) along with each of these functional paths. Animations are provided in the first part. The second part uses the same illustrations with a number-and-key system to assist the students in learning the location of various portions of the pathway. This PowerPoint-based resource is used to supplement either traditional gross anatomy and/or neuroscience course material, as well as to support case-based learning approaches. This resource reinforces what is often considered a very difficult and convoluted pathway. Earlier versions of this program have been used by students to initially learn and then review the material. Students have commented that it's nice to have access to this autonomic module on a "need to know" availability.